Revealing fitness and virulence determinants of hypervirulent Klebsiella pneumoniae during infection in Galleria mellonella using a transposon library - Xiao, Lisheng; Nie, Zihan; Zhuang, Deyi; Zhou, Yufeng; Zhu, Weiwei (Frontiers in Cellular and Infection Microbiology, 2025)
Klebsiella pneumoniae infections represent a significant public health concern. Despite their clinical relevance, the genetic determinants underlying bacterial fitness and virulence remain incompletely characterized. In this study, we systematically identified genes involved in host adaptation by generating a transposon mutant library and integrating a Galleria mellonella infection model with transposon sequencing (Tn-seq) technology. This approach yielded a comprehensive dataset of adaptation-deficient genes in the hypervirulent K. pneumoniae strain ATCC 43816. Using homologous recombination, we constructed gene deletion mutants of the carbohydrate phosphotransferase system enzyme I (PtsI) and the putative prolyl endopeptidase (GM2628), and verified their key roles in K. pneumoniae fitness and virulence through both in vitro and in vivo assays. In particular, ptsI defects exhibited lower dissemination and virulence in a murine pneumonia model, which cross-validates that the virulence determinants identified by the G. mellonella model are conserved across hosts. Our findings provide gene-level insights for the development of novel strategies to combat K. pneumoniae infections and indicate that G. mellonella is a cost-effective mammalian alternative for investigating bacterial pathogenicity. Going beyond the general knowledge that hypermucoviscosity (HMV) mediates high virulence, we observed that deficits in ptsI and GM2628 led to HMV while decreasing virulence. This exemplifies that HMV does not always directly correlate with virulence, challenging its role as a virulence marker and underscoring the need for further investigation into non-HMV-mediated virulence mechanisms.